THE COMBINATION OF DRAGON FRUITS SKIN AND TEAK LEAVES ANTHOCYANIN EXTRACT AS SOYMILK’S NATURAL DYE - & et al., Wahyuni (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Natural dye is easier to dissolve in water and to be absorbed by our body than artificial pigment. Anthocyanin pigment combination from different sources is able to improve functional food quality. Soymilk is a white liquid vegetarian functional food which hasn’t adorable appearance. The dragon fruit skin and teak leaves anthocyanin extract combination can be used as alternative natural pigment to improve soymilk’s quality. Dragon fruit skins bright red, while the teak leaves is dark red with higher anthocyanin content. This study aimed to determine the dragon fruit skin and teak leaves anthocyanin extract combination to Argomulyo var. soymilk’s quality. Completely Randomized Design (CRD) one factor (dragon fruit skin and teak leaves extract combination) with 3 levels (5%, 10%, and 15%) were applied. The experiments consisted of two main process, the first step was anthocyanin extraction which followed by soymilk’s production. Dragon fruit skin and teak leaves anthocyanin extraction used maceration method with water as solvent through blanching process at 80oC. Soymilk’s color intensity measured by color reader, organoleptic (hedonic-test), pH (pH-meter), anthocyanin (pH differential and UV-Vis spectrophotometer), and antioxidants activity (DPPH). The result showed that 15% anthocyanin addition gave the best results with redness (8.39), yellowness (3.24), brightness (41.33), organoleptic color (4.15), pH (6.54), anthocyanin (4.007 mg/L), and antioxidant (69.13%).